Improving the quality of life of patients with breast cancer-related lymphoedema by lymphaticovenous anastomosis (LVA): study protocol of a multicentre randomised controlled trial - Wolfs, Joost (BMJ Open, 2020)
INTRODUCTION: Early breast cancer detection and advancements in treatment options have resulted in an increase of breast cancer survivors. An increasing number of women are living with the long-term effects of breast cancer treatment, making the quality of survivorship an increasingly important goal. Breast cancer-related lymphoedema (BCRL) is one of the most underestimated complications of breast cancer treatment with a reported incidence of 20%. A microsurgical technique called lymphaticovenous anastomosis (LVA) might be a promising treatment modality for patients with BCRL. The main objective is to assess whether LVA is more effective than the current standard therapy (conservative treatment) in terms of improvement in quality of life and weather it is cost-effective. METHODS AND ANALYSIS: A multicentre, randomised controlled trial, carried out in two academic and two community hospitals in the Netherlands. The study population includes 120 women over the age of 18 who have undergone treatment for breast cancer including axillary treatment (sentinel lymph node biopsy or axillary lymph node dissection) and/or axillary radiotherapy, presenting with an early stage lymphoedema of the arm, viable lymphatic vessels and received at least 3 months conservative treatment. Sixty participants will undergo the LVA operation and the other sixty will continue their regular conservative treatment, both with a follow-up of 24 months. The primary outcome is the health-related quality of life. Secondary outcomes are societal costs, quality adjusted life years, cost-effectiveness ratio, discontinuation rate of conservative treatment and excess limb volume. ETHICS AND DISSEMINATION: The study was approved by the Ethics Committee of Maastricht University Medical Center (METC) on 19 December 2018 (NL67059.068.18). The results of this study will be disseminated in presentations at academic conferences, publications in peer-reviewed journals and other news media. TRIAL REGISTRATION NUMBER: NCT02790021; Pre-results.